Analisis Pengaruh Faktor Fundamental terhadap Harga Saham Sebelum dan Selama Pandemi Covid-19 - Putri Awalina; Imarotus Suaidah; Miladiah Kusumaningarti (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
This study aims to find empirical evidence of the influence of the current ratio, fixed asset turnover, debt to equity ratio, and return on assets on stock prices. The sample in this study amounted to 36 companies taken from a population of 42 companies in the hotel, restaurant and tourism sub sector listed on the Indonesia Stock Exchange in 2019 and 2020. Determination of the number of samples was carried out by purposive sampling method. The research data were analyzed using multiple linear regression analysis with the help of SPSS. Testing was carried out separately between data for 2019 and data for 2020. Data for 2019 shows conditions before the covid-19 pandemic, while data for 2020 shows condition during the covid-19 pandemic. The result of the study found empirical evidence that the current ratio, fixed assets turnover, and return on assets had e effect on stock prices in both condition. Meanwhile, the debt to equity ratio has an effect but is not in accordance with the exixting theory where the debt to equity ratio has a negative effect on stock prices. In this study, the debt to equity ratio has a positive effect, this indicate that the company’s capital structure uses more funds provided by creditors to generate profits.